Participatory Learning and Action for Environmental Education - Sudhir, M.A. (INDIAN EDUCATIONAL REVIEW, 2013)
Environmental education is the means to create knowledge, understanding, values, attitudes, skills, abilities and awareness among individuals and social group towards the environment and environment protection. The school system provides the largest organised base for environmental education and action. With children in their plastic age, school imparts knowledge for imbibing in them the environmental ethics and consciousness. Teacher is one of the important factors for promoting environmental education. Teachers can become a vital link in the delivery of environmental knowledge, its associated problems and their solutions